CHEOPS observations of TESS primary mission monotransits. Issue 1 (18th March 2020) - Cooke, Benjamin F; Pollacco, Don; Lendl, Monika; Kuntzer, Thibault; Fortier, Andrea
ABSTRACT: We set out to look at the overlap between CHaracterizing ExOPlanets Satellite ( CHEOPS ) sky coverage and Transiting Exoplanet Survey Satellite ( TESS ) primary mission monotransits to determine what fraction of TESS monotransits may be observed by CHEOPS . We carry out a simulation of TESS transits based on the stellar population in TICv8 in the primary TESS mission. We then select the monotransiting candidates and determine their CHEOPS observing potential. We find that TESS will discover approximately 433 monotransits during its primary mission. Using a baseline observing efficiency of 40 per cent, we then find that 387 of these (∼89 per cent) will be observable by CHEOPS with an average observing time of ∼60 d yr −1 . Based on the individual observing times and orbital periods of each system, we predict that CHEOPS could observe additional transits for approximately 302 of the 433 TESS primary mission monotransits (∼70 per cent). Given that CHEOPS will require some estimate of period before observing a target, we estimate that up to 250 (∼58 per cent) TESS primary mission monotransits could have solved periods prior to CHEOPS observations using a combination of photometry and spectroscopy.